Improving aerobic performance - Kovacs, M.; Lemus, M. (Conditioning for strength and human performance, 2013)
Aerobic exercise is important for athletes in any sport that requires training or competition over an extended period of time (i.e., >3 to 5 minutes). It is unclear, however, the extent to which traditional aerobic exercise is necessary for athletes in nonendurance sports (e.g., football, baseball, basketball). With explosive nonendurance athletes (speed, power, and strength sports), where performance is measured over a matter of a few seconds or less, the case has been made that aerobic fitness is important for recovery from competition and training (since we use the oxidative system to recover from anaerobic training) and that aerobic energy pathways may contribute to anaerobic performance (1).